Implementasi Kurikulum Merdeka Sebagai Wujud Pembelajaran Abad 21 Dalam Meningkatkan Profil Pelajar Pancasila Sekolah Dasar - Dahlan, Taufiqulloh; Aisyah, Marsha Anadia; Nabila Kusumah, Githania Anggian; Salsabila , Najwaa Riffa; Agustiani, Hilyatul Aulia; Rizki Meilani, Elsa Dwi (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
This study analyzes the implementation of the Merdeka Curriculum in elementary schools as a form of 21st-century learning to improve the Pancasila Student Profile. The research method used a literature study by collecting and analyzing data related to learning practices, 21st-century skills development, and character building in students. The results show that the Merdeka Curriculum provides flexibility in learning management, facilitates project-based activities, and adapts strategies to student needs. This approach supports the development of critical thinking, creativity, collaboration, as well as student responsibility and independence. The involvement of parents and the school environment also strengthens the internalization of character values. These findings confirm that the Merdeka Curriculum shapes students who are academically competent and have character in accordance with the Pancasila Student Profile. Keyword: Merdeka Curriculum, 21st Century Learning, Pancasila Student Profile, Elementary School, Project-Based Learning.